2019
DOI: 10.1080/21870764.2019.1595930
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-containing apatite fiber scaffolds with enhanced mechanical property express osteoinductivity and high osteoconductivity

Abstract: We began this study by synthesizing apatite fibers (AFs) and silicon-containing apatite fibers (Si-AFs) using a homogeneous precipitation method. Next, we have successfully fabricated three-dimensional apatite fiber scaffolds (AFSs) and silicon-containing apatite fiber scaffolds (Si-AFSs) using the above the AFs and Si-AFs, respectively. Finally, we successfully enhanced the mechanical properties of the scaffolds using carbon beads (CBs) with diameters of 20 μm and 150 μm, and conducted uniaxial pressing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…The results from the duplicate experiments were in good agreement, showing 2% difference from the first experiment for the specimens with PLGA added. In another study, we reported that bioceramics with a porosity of 70% produced osteoinduction after implantation in porcine muscle [ 27 ]. The porosity of the cement specimens in this study were also generally around 70%, and the specimens were therefore expected to show osteoinduction.…”
Section: Resultsmentioning
confidence: 99%
“…The results from the duplicate experiments were in good agreement, showing 2% difference from the first experiment for the specimens with PLGA added. In another study, we reported that bioceramics with a porosity of 70% produced osteoinduction after implantation in porcine muscle [ 27 ]. The porosity of the cement specimens in this study were also generally around 70%, and the specimens were therefore expected to show osteoinduction.…”
Section: Resultsmentioning
confidence: 99%
“…The material properties, crystallite sizes, and second selected FT-IR wavenumbers were predicted from the synthesis conditions. The plots of the actual values versus the predicted values of method 7 in DCV are shown in Figure 4, and their r DCV 2 and MAE DCV values are given in Table 3. Because the points are close to the diagonal for all of the features, the values can be predicted by GMR with high accuracy.…”
Section: Modelmentioning
confidence: 99%
“…However, the resulting material may lack various important ions, such as magnesium, natrium, potassium, silicon, strontium, and iron [ 50 , 51 , 52 , 53 ]. Table 1 summarizes the biological effects of different trace elements identified in previous studies [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The ready availability of important ions in xenograft, such as from mammalian bone, or fish bone and scale, as well as its low processing cost, makes it a preferred option for biomedical applications research [ 80 ].…”
Section: Natural Hydroxyapatite Compared To Synthetic Hydroxyapatitementioning
confidence: 99%